Español - Vindas Porras, Johanna (2020)
At present Hypertrophic Cardiomyopathy (HCM) is one of the most common hereditary cardiac conditions. It is defined as a cardiac muscle disorder inherited as an autosomal dominant disease with variable expression, caused by mutations in one of several sarcomere genes leading to an unexplained and abnormal left ventricular (LV) thickening usually asymmetrical, that lacks chamber dilation and it is linked to myocyte disarray and fibrosis. Diagnostic assessment of HMC is most often made via echocardiographic evaluation identifying the left ventricular hypertrophy (LVH), estimating changes in the left ventricular outflow tract gradients, systolic and diastolic performance, and mitral valve (MV) structure and function.  In reference to management strategies: surgical myectomy or alcohol septal ablation are used for attenuating outflow obstruction and symptoms of heart failure, the colocation of an implantable defibrillator to prevent sudden death and the use of drugs to control and prevent atrial fibrillation and stroke.